"What Does One Feel Being the Apple". Body and Gestural Knowledge Seen Through Contemporary Dance - Donato, Simona (Aesthetica Preprint, 2022)
The main thesis of this essay is that contemporary dance is a privileged place to ask the question of what it feels like to be and to have a body in motion among other bodies. Therefore, it is not just an activity restricted to a specific professional field: movement, space, time, rhythm, gesture and gravity concern every human being. Contemporary dance shows us, in fact, in an intensified way, some aspects of that paradoxical experience of always finding ourselves in the duplicity between a thinking instance and a moving and acting one, which tradition has called ‘mind’ and ‘body’. I also argue that Garroni’s philosophical framework is appropriate to critically examine the increasingly emergent and inevitable question of understanding bodily and gestural knowledge, those knowledges that inhabit our senses, but also our movements, our gestures, of which we are, often, unaware. In particular, in this essay, I give the example of Contact-Improvisation, one of the most revolutionary contemporary dance techniques, which reveals to us a fundamental and only partially conscious body knowledge: weight or gravity, not from a biomechanical point of view, but from that of the experience we have of it as earthlings.